DETECTION OF EATING DISORDERS RISKS AMONG 12TH GRADE STUDENTS - Fokina, Olga; Vaivodiša, Anželika; Deklava, Liāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The attitude to the healthy eating and eating habits takes its roots in the family. When becoming a grown-up, a person prefers eating the favorite and habitual food. It depends only on a person’s own choice to observe the basic laws of the healthy eating and keeping to them and in this way to support own health. As opposed to healthy, balanced, diversified, regular and sufficient amount of food there are the strategies that can cause eating disorders if to follow them. Among such disorders might be neurotic anorexia, neurotic bulimia, compulsive overeating and other unspecified eating disorders. The prevalence of eating disorders nowadays is connected with the influence of increased stress, an enlarged information load, an awareness of modern beauty standards as a result, eating disorders risks are increasing. Prompt information and provision of knowledge for teachers, parents and students on eating disorders prevalence, manifestation and the importance of timely recognition for successful treatment is the most important element of preventive measures. The topicality of the research on eating disorders among students is justified by the fact that the early detection of students’ eating disorders can promote timely recognition of the problem and the beginning of treatment reducing serious physical and psychological complications and even fatal cases. The primary goal of this research was to find out eating disorders risks among the 12th grade students. The second goal was to determine eating disorders risks among the 12th grade students due to the gender differences of students. To gain the results of the research the quantitative research method with the research tool – EAT-26 test (Garner et al., 1982) was used. Two hundreds of the 12th grade students were involved into the research as respondents. The results of the survey show that the 5th part of the respondents have got eating disorders risks indicators. There are statistically significant differences between men and women (р<0.001).